(untitled) (Orthodontic Journal of Nepal, 2018)
Forsus is a Class II corrector appliance used in growing as well as in young adults. Proclination and forward movement of lower incisor is the major drawback reported using this appliance. Forsus results in Class II correction mainly through dentoalveolar effect and minimal skeletal effect. We used a new innovation incorporating miniscrew assisted laceback to minimize lower incisor proclination. Utilization of miniscrew assisted laceback effectively reduces the unfavorable proclination and allows additional skeletal effects. This method applies a distal driving force on the lower anteriors, which minimizes lower incisor proclination. It is proven to be effective method in controlling the lower incisor flaring.